Study on Void Reactivity of Supercritical Carbon Dioxide Cooled Reactor - LIU Minyun;CUI Rongyi;ZHAO Xingyu;HAN Wenbin;HUANG Shanfang;HUANG Yanping (Yuanzineng kexue jishu, 2023)
Due to the weak moderating capability of carbon dioxide itself, supercritical carbon dioxide cooled reactor typically has a hard energy spectrum and is susceptible to safety issues introduced by positive reactivity feedback in the event of LOCA (loss of coolant accident). In this paper, based on the energy spectrum characteristics of supercritical carbon dioxide reactor, a three-factor formula was proposed to describe the neutron circulation process. Based on the analysis of the threefactor formula, the effective fission neutron number and neutron utilization factor were refered as spectral terms in this study, while the probability of no leakage was referred as the leakage term. When studying the effect of moderator, fuel burnup, etc. on the void reactivity, the energy spectrum factor was mainly considered. When studying the effect of radial reflector material, high radial ratio, etc. on the void reactivity, the leakage factor was mainly considered, providing guidance for the core design of supercritical carbon dioxide reactors based on this theoretical basis. Using Monte Carlo simulation method, modeling, verification, and analysis were carried out for the supercritical carbon dioxide cooled reactor design proposed by MIT. The fuel assemblies of this reactor adopt a hexagonal annular fuel design, with the center of the assembly being the SCO2 coolant channel, which is separated from the MOX fuel by a cladding. A total of 265 fuel rod assemblies arranged in a hexagonal pattern make up a fuel component, and 562 fuel components (divided into three zones) and 21 control rod components arranged in a hexagonal pattern make up the reactor core active zone. Axial and radial reflector layers are set outside the active zone, and the outermost layer is a B4C absorber. The height of the active zone is 1.54 m, and the effective diameter is 4.81 m, with a height-to-diameter ratio of H/D=0.32 and a thermal power output of 2 400 MW. The results show that the design of supercritical carbon dioxide reactor needs to focus on the softening of energy spectrum and reasonable core geometry design. Using supercritical carbon dioxide as the radial reflector layer, in the event of LOCA, the carbon dioxide as the reflector and the carbon dioxide inside the core will leak simultaneously, and the increase in core leakage rate will lead to a decrease in void reactivity. Compared with other materials such as BeO, PbO, and SiO2, using a carbon dioxide reflector layer can better ensure the criticality of the core and improve neutron economy. However, due to the generally low neutron reflection ability of supercritical carbon dioxide itself, if the core has a large radial leakage due to a high core-to-diameter ratio, a thicker radial reflector layer is required, which may bring additional engineering difficulties and costs, requiring balance in the design. Setting moderators by partition can flatten the neutron flux, soften the energy spectrum, and reduce the reactivity introduced by LOCA.